RECONSTRUCTION OF ISLAMIC FAMILY LAW IN THE FIELD OF LEGAL INHERITANCE IN RELIGIOUS PLURALISM AND ITS CONTRIBUTION TO NATIONAL LAW (Ijtihad Study Of Judges Of Religious Court On Development Of Inheritance Law In The Compilation Of Islamic Law) - ahmad khisni (International Journal of Law Reconstruction, 2017)
The juridical-theological-philosophical distinction of religion is one of the obstacles of a person to be an heir. On the other hand, empirically-historically-sociologically isnot so, because of the existence of illat or other reasons that allow a person of different religions to gain inheritance from the heirs who are Muslims by considering the factors of justice. It is an act of makrufconstructive ‘wasiatwajibah’ to the relatives in need and oriented towards human values, usefulness and benefit which need to be realized in pluralist society of diverse life. It can contribute to the national law which is the result of ijtihad in the form of development of compilation The Islamic Law texts (tahrij al-ahkam 'alanash al-qanun) as a form of legal discovery with a progressive paradigm in realizing the function of the judiciary that the judiciary is a tool of social change.